Le capital environnemental : esquisse d’une notion pour la compréhension des dynamiques socio-environnementales - Christophe Beaurain; Romain Rouaud; Paul Arnould (Développement Durable et Territoires)
This special section dedicated to the notion of "environmental capital" comes from a conference organized in Limoges in November 2015. This notion is defined as all investments (socio-economic, ideological, emotional, political, artistic…) in the environment realized by actors. This notion mainly reveals the potential influence of social conditions (relationships of domination, inequalities, forms of exclusion…) structuring the interactions resulting from these individual commitments to the environment. In this introduction, we specify the epistemological sources of this notion and underline its heuristic interest by some examples.